Causes and Impacts of Job Displacements and Public Policy Responses - Schmillen, Achim D. (World Bank, Washington, DC, 2020)
Across the globe, both cyclical downturns and structural changes episodically eliminate substantial numbers of jobs and in the process create serious dislocations. For instance, the rise in joblessness because of the ongoing COVID-19 crisis is projected to be extraordinarily steep. As a response to job displacements, governments have implemented a range of measures to financially compensate displaced workers, assist them in finding reemployment, or both. The challenges should not be minimized: job losses have significant economic as well as social and psychological consequences; laid-off workers often lack the skills or geographic proximity to easily transfer to sectors that are growing; and providing adequate support can be expensive. Nonetheless, careful public policy responses can help mitigate the costs of job displacements and support workers in finding productive reemployment.